Merits and pitfalls of currently used diagnostic tools in mycetoma - Reynolds, Todd; Van de Sande, Wendy W. J.; Fahal, Ahmed Hassan; Goodfellow, Michael; Mahgoub, El Sheikh; Welsh Lozano, Oliverio; Zijlstra, Ed E. (Public Library of Science, 2014)
Treatment of mycetoma depends on the causative organism and since many organisms, both actinomycetes (actinomycetoma) and fungi (eumycetoma), are capable of producing mycetoma, an accurate diagnosis is crucial. Currently, multiple diagnostic tools are used to determine the extent of infections and to identify the causative agents of mycetoma. These include various imaging, cytological, histopathological, serological, and culture techniques; phenotypic characterisation; and molecular diagnostics. In this review, we summarize these techniques and identify their merits and pitfalls in the identification of the causative agents of mycetoma and the extent of the disease. We also emphasize the fact that there is no ideal diagnostic tool available to identify the causative agents and that future research should focus on the development of new and reliable diagnostic tools.